Documentation and description of the Afro-Portuguese Creole spoken on the island of Fogo (Cape Verde, West Africa) - (:unkn) unknown (My University, 2020)
This thesis is the first book-length description of the Portuguese Creole spoken on the island of Fogo (Cape Verde, West-Africa), spoken by most of the 40,000 island’s inhabitants as well as by its diaspora. This work provides an insight on the linguistic structure of this variety, based on data collected during fieldwork occurred between 2016 and 2019. This study comprises with nine chapters, namely (1) introduction, (2) phonology, (3) syllabic structure, (4), stress, (5) nominal morphology, (6) verbal morphology, (7) syntax, (8) lexical peculiarities and (9) conclusion.This thesis brings new elements both to the synchronic and diachronic analysis of Cape Verdean Creole. At the same time, it contributes with comparative data for the reconstruction of the Upper Guinea Portuguese Creole (UGPC) language family. These data show in particular that Fogo Cape Verdean emerged quite early as a distinct variety among UGPCs and illustrate the main characteristics of this variety.This thesis also provides historical data on the discovery, settlement, trade connections, maritime interactions, social structure and sociolinguistics of the island of Fogo, and shows the role played by these elements in the development and shaping of Fogo’s unique linguistic makeup.
Keywords: African Research